Standardization Of Beef Randang Recipes as Traditional Food In Nagari Gaduik Kecamatan Tilatang Kamang District Agam - Nibras Nibras; Elida Elida (Universitas Negeri Padang, 2021)
This study aims to standardize the beef randang recipe, identify the ingredients used for the production of beef randang, identify the equipment used, explain the processing process, and describe the function of the beef randang in the Gaduik village. This type of research is a descriptive study with a qualitative approach method. Data collection techniques were carried out in the form of observation, interviews, and documentation in the field. After data collection, the authors obtained specific research findings, these findings were in accordance with the research objectives, the first was about the ingredients for making beef randang in the form of: meat, coconut milk, shallots, garlic, ginger, galangal, lemongrass, coriander, turmeric leaves, and , lime leaves, leave salam, red chilies, roasted coconut, nutmeg, turmeric, tamarind, and salt. The second finding is in the form of tools used in processing, namely: iron cauldrons, milled stones, clay stoves, stone stoves, and spoons. Furthermore, the processing process starts from material preparation until it is ready to be served. Finally, the function of the beef randang is served at events such as wedding receptions, Islamic holidays, Eid al Fitr celebrations, Eid al-Adha celebrations and meals for visits from officials.